ANALYSIS AND THEORETICAL STUDY PROCESS POLLUTION OF SURFACE WATERS MIKROZABRUDNYUVACHAMY (Municipal economy of cities (Technical science), 2013)
Research mikrozabrudnyuvachiv (metals) in water r.Udy (Kharkiv region). Conducted using standard and passive sampling. The results suggest that the definition of micro-pollutants are the most effective passive sampling methods.